Low voltage ride through enhancement using grey wolf optimizer to reduce overshoot current in the grid-connected PV system - N., Jaalam; A.Z., Ahmad; A.M.A., Khalid; R., Abdullah; N., M.Saad; S., A.Ghani; L. N., Muhammad (Hindawi Publishing Corporation, 2022)
In today's world, the DG should not be disconnected in the event of a power outage but should instead remain linked to the grid and supported by reactive power. This can be accomplished by implementing the low voltage ride through (LVRT) with a proportional integral (PI) controller. As a result, the voltage profile can be enhanced. The PI controller, on the other hand, has drawbacks in that setting the gain takes a long time and results in an overshoot current on the grid, which could trigger the protection relay. To address this issue, this paper proposes employing a grey-wolf optimizer (GWO) to enhance the LVRT in a 5 MW three-phase grid-connected PV system. A MATLAB simulation was carried out then under a three-phase fault and load disturbance to verify the efficiency. It is found that, even with a 70% voltage sag, the PV system can remain connected to the electrical grid while minimising overshoot current on the grid side.